Mediterranean landscapes in post antiquity : new frontiers and new perspectives - Gelichi, Sauro,; Olmo Enciso, Lauro, (Archaeopress archaeology., 2019)
The study of landscape has in recent years been a field for considerable analytical archaeological experimentation. Although the Mediterranean is the home of classicism, it has seen the implementation of projects of this new kind, and in regions of Spain and Italy, after some delay, the proliferation of landscape archaeology studies.